2021
DOI: 10.1186/s12891-021-03999-y
|View full text |Cite
|
Sign up to set email alerts
|

Monocortical fixation for locking plate distal screws does not impair mechanical properties in open-wedge high tibial osteotomy

Abstract: Background The neurovascular bundle containing the deep peroneal nerve has a potential risk of injury during open-wedge high tibial osteotomy (OWHTO), particularly due to drilling for bicortical fixation at distal screw holes. Therefore, monocortical fixation is recommended for distal fixation of a long locking plate as long as good stability is ensured. The purpose of this study was to analyse the biomechanical properties of monocortical fixation of distal locking screws for OWHTO. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…To avoid this risk, mono‐cortical fixation of several of the distal screws is recommended. Finite element analysis of mono‐cortical fixation for three distal screws (2, 3, and 4) of the locking plate showed no impairment of biomechanical stability as compared with bi‐cortical fixation for all four distal screws in OWHTO 14 . However, the mechanical properties of the tibia after OWDTO are different from those after OWHTO, particularly the anterior osteotomy line that is located on the diaphysis in OWDTO, while it is located on the metaphysis in OWHTO.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…To avoid this risk, mono‐cortical fixation of several of the distal screws is recommended. Finite element analysis of mono‐cortical fixation for three distal screws (2, 3, and 4) of the locking plate showed no impairment of biomechanical stability as compared with bi‐cortical fixation for all four distal screws in OWHTO 14 . However, the mechanical properties of the tibia after OWDTO are different from those after OWHTO, particularly the anterior osteotomy line that is located on the diaphysis in OWDTO, while it is located on the metaphysis in OWHTO.…”
Section: Discussionmentioning
confidence: 90%
“…Finite element analysis of mono‐cortical fixation for three distal screws (2, 3, and 4) of the locking plate showed no impairment of biomechanical stability as compared with bi‐cortical fixation for all four distal screws in OWHTO. 14 However, the mechanical properties of the tibia after OWDTO are different from those after OWHTO, particularly the anterior osteotomy line that is located on the diaphysis in OWDTO, while it is located on the metaphysis in OWHTO. To the best of our knowledge, no study has presented any investigation of the stability of mono‐cortical fixation of distal screws in OWDTO.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 For locking screws, cross-threading between the screw head and plate hole threads provides enough angular stability for unicortical application, 10 but the construct resistance may not be the same when the locking screw is applied bicortically. [12][13][14] The use of only locking screws has also been suggested for PIP arthrodesis, 4 with retrospective studies reporting the use of bicortical screws in the proximal plate hole without describing potential risks of peri-implant fractures. 15,16 In a meta-analysis, de Souza and colleagues found that 65% of horses undergoing PIP arthrodesis (using different implants) returned to their activities.…”
Section: Introductionmentioning
confidence: 99%